2023
DOI: 10.3390/su15065323
|View full text |Cite
|
Sign up to set email alerts
|

Large-Deformation Failure Mechanism and Stability Control of a Swelling Soft Rock Roadway in a Sea Area: A Case Study in Eastern China

Abstract: Coal mining in sea areas has higher requirements for geological support systems, technical equipment levels, and safety production capacities because of the complex engineering geological conditions of underwater coal mines. In this paper, the deformation failure mechanism and stability control of a typical swelling soft rock roadway in the Beizao coal mine in a sea area are studied. A series of mechanical experiments and theoretical analyses were conducted to research the mechanical properties and reasons for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…Currently, coal remains the primary energy source for meeting China's energy requirements, a position unlikely to change in the foreseeable future [1]. With the deepening of mining operations, deep soft rock mines encounter persistent high stress and multiple hazardous environments, posing significant threats to the safe extraction of coal resources [2][3][4]. The Ordos Basin, located in the western region of northern China, boasts substantial coal reserves.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, coal remains the primary energy source for meeting China's energy requirements, a position unlikely to change in the foreseeable future [1]. With the deepening of mining operations, deep soft rock mines encounter persistent high stress and multiple hazardous environments, posing significant threats to the safe extraction of coal resources [2][3][4]. The Ordos Basin, located in the western region of northern China, boasts substantial coal reserves.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [29] revealed the phenomenon, and nature and the factors contributing to substantial deformation in deep soft rock roadways were investigated, leading to the proposition of appropriate measures for supporting the infrastructure. Dong et al [30] conducted a comprehensive examination into the mechanical characteristics and causative factors of damage in expanding soft rock roadways. Liu et al [31] and Liu et al [32] used CT scanning technology to study the damage information and damage process of sandstone under pressure.…”
Section: Introductionmentioning
confidence: 99%